1999
DOI: 10.1017/s0007114599001622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inulin on faecal bifidobacteria in human subjects

Abstract: A controlled study with eight healthy free-living subjects was carried out, in which energy intake was adjusted to the individual energy requirements. On administration of inulin, blood lipids, the faecal microflora, short-chain fatty acids and accompanying gastrointestinal symptoms were characterized in order to investigate the long-term effect of inulin. During the run-in phase (8 d), subjects received a typical Western diet providing 45 % energy as fat and 40 % energy as carbohydrate. Subsequently, the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
120
4
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(143 citation statements)
references
References 38 publications
16
120
4
3
Order By: Relevance
“…Previous human feeding studies have demonstrated the bifidogenic nature of both inulin and oligofructose. A variety of doses have been thus far reported effective in increasing faecal bifidobacteria in vivo, ranging from 4 to 40 g/day (Williams et al, 1994;Gibson et al, 1995;Buddington et al, 1996;Kleessen et al, 1997;Bouhnik et al, 1999;Kruse et al, 1999;Den Hond et al, 2000;Tuohy et al, 2001a;Bouhnik et al, 2004). Although microbial culture techniques were used in the majority of studies, results reported thus far on the prebiotic efficacy of inulin and oligofructose are in agreement with studies employing molecular methodologies of monitoring the prebiotic effect on the bacterial microflora (Tuohy et al, 2001a, b).…”
Section: Introductionsupporting
confidence: 53%
“…Previous human feeding studies have demonstrated the bifidogenic nature of both inulin and oligofructose. A variety of doses have been thus far reported effective in increasing faecal bifidobacteria in vivo, ranging from 4 to 40 g/day (Williams et al, 1994;Gibson et al, 1995;Buddington et al, 1996;Kleessen et al, 1997;Bouhnik et al, 1999;Kruse et al, 1999;Den Hond et al, 2000;Tuohy et al, 2001a;Bouhnik et al, 2004). Although microbial culture techniques were used in the majority of studies, results reported thus far on the prebiotic efficacy of inulin and oligofructose are in agreement with studies employing molecular methodologies of monitoring the prebiotic effect on the bacterial microflora (Tuohy et al, 2001a, b).…”
Section: Introductionsupporting
confidence: 53%
“…Although resistance to inulin and other prebiotics is low, it appears that the gut microbiota exhibits resilience following the conclusion of treatment. Kruse et al showed that 34 days after a 64-day treatment period, Bifidobacterium population sizes in 8 human subjects began to return to the levels observed before treatment (179). Studies of the mouse gut microbiota also suggest that prebiotic effects are short-lived.…”
Section: Resistance and Resiliencementioning
confidence: 99%
“…Interassay CV was 4.7%. Butyric acid was quantified by a modified version of a method described previously [31] and analysed by gas chromatography (HP 5890 II GC; Hewlett-Packard, Böblingen, Germany) using a capillary column (HP-20M; Hewlett-Packard, Palo Alto, CA, USA) and a flameionisation detector.…”
Section: Test Mealsmentioning
confidence: 99%